A role for a novel protein, nucleolin, in Parkinson's disease - Caudle, W. Michael; Kitsou, Efstathia; Li, Jane; Bradner, Joshua; Zhang, Jing (Neuroscience letters, 2009)
Although much has been learned in the last few decades concerning the molecular mechanisms and pathways associated with the development of familial as well as sporadic Parkinson disease (PD), the precise mechanisms and specific proteins responsible for mediating these effects remain to be elucidated. Thus, the identification and biological evaluation of novel proteins involved in these pathways is critical to providing a more comprehensive understanding of PD pathogenesis. Previously, in a cellular model of PD, we identified nucleolin as a protein interacting with α-synuclein and DJ-1, two critical proteins involved in PD pathogenesis. In our current study, we found the expression levels of nucleolin were dramatically reduced in the substantia nigra pars compacta of human PD subjects, compared with controls. Furthermore, manipulation of nucleolin in an in vitro model of PD resulted in significant alterations in the generation of oxidative stress as well as proteasomal inhibition following rotenone exposure. Interestingly, nucleolin expression did not influence mitochondrial complex I activity, suggesting a selective specificity for oxidative stress and proteasomal pathways.